Pencegahan Bullying Di Mi Islamiyah Kayulemah Bojonegoro - Linda Nur Afrida; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Cases of violence and bullying in schools still frequently occur and negatively affect students’ psychological conditions and educational quality. This study aims to describe and analyze the synergistic efforts between the Department of Education and schools in preventing and handling violence in the learning environment. This research used a descriptive qualitative approach. The study was conducted at MI Islamiyah Kayulemah, Sumberjo District, Bojonegoro Regency from February to April 2026. Data were collected through in-depth interviews with the principal, homeroom teachers, and the Department of Education, as well as field observations and documentation related to the Violence Prevention and Handling Team (TPPK). Data analysis used the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results showed that the Department of Education acts as a regulator through child-friendly school policies, anti-bullying socialization programs, and strengthening the establishment of TPPK in schools. Meanwhile, schools implement these policies through character building, counseling services, student behavior supervision, and parental involvement in bullying prevention. This study concludes that synergy between the Department of Education, schools, and parents can create a safer and more comfortable learning environment for students.